Financial Management of Indonesian Democratic Party-Struggle (Partai Demokrasi Indonesia-Perjuangan/PDPI) in the District of Jepara and efforts in increasing public trust (JPPUMA: Jurnal Ilmu Pemerintahan dan Sosial Politik UMA (Journal of Governance and Political Social UMA), 2020)
This study aims to know the financial management of the Indonesian Democratic Party-Struggle (Partai Demokrasi Indonesia-Perjuangan) in the District of Jepara Regency and its connection to public trust. The financial management in the party determines its existence and electability in the political field. To increase the party‘s electability and to maintain the confidence of its members and public trust, financial transparency should be improved. Financial transparency of the political party is still beyond the expectations. Ideally, as a public institution, Indonesian political parties have a very large role in maintaining democracy and good governance. This research investigates the Branch (Dewan Pimpinan Cabang) of the Indonesian Democratic Party-Struggle (PDI-P) in the district of Jepara, Central Java. This party won the 2014 General Election in the district. Although, its financial management is not transparent. This research applies quantitative methods to portray the phenomenon. This research chose 100 people as samples from the total population of the Jepara District who has the right to vote. The sample has been taken by probability sampling techniques. The results show that DPC-PDIP in Jepara District manages its finance with discipline and following law. PDIP is considered to know about good financial reporting. This increases public trust and the party‘s confidence.